Minimizing total Completion Time and Maximum late Work Simultaneously - Abdul-Razaq, T. S.; Fandi, F. Sh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, the problem of scheduling jobs on one machine for a variety multicriteria are considered to minimize total completion time and maximum late work. A set of n independent jobs has to be scheduled on a single machine that is continuously available from time zero onwards and that can handle no more than one job at a time. Job i,(i=1,…,n) requires processing during a given positive uninterrupted time pi, and its due date d i. For the bicriteria problems, some algorithms are proposed to find efficient (Pareto) solutions for simultaneous case. Also for the multicriteria problem we proposed general algorithms which gives efficient solutions within the efficient range